Menstrual hygiene management inequalities among school girls in Badagry, Nigeria - Ruth C. Uwadia (14779633) (2023)
Objectives The study assessed menstrual hygiene management (MHM) inequalities among public and private in-school adolescents in Badagry, southwest Nigeria. Also assessed was the impact of available water, sanitation and hygiene (WASH) facilities on MHM within the school premises. Methods For this descriptive cross-sectional study, 420 students were selected via multi-stage sampling and data were obtained via a validated semi-structured questionnaire and observational checklist. Data were analysed at 95% confidence limit. Results The students had a mean age of 15.3 ± 1.6 years. All the private schools had functioning WASH facilities whereas only 50% of public schools did. The toilet to student ratios for the private and public schools were 1:155 and 1:296, respectively. Over two-thirds (67.1%) of the students reportedly use sanitary napkins for MHM, followed by tissue (17.1%) and clothes (15.5%). Additionally, the private school students were two times less likely to use alternatives to sanitary napkins and 9.8 times more likely to obtain sanitary materials at school if required (p < 0.001). A significantly higher proportion of public-school menstruating in-school adolescents changed their sanitary towels in the bush (p = 0.003) due to lack of privacy and took their used sanitary materials home (p < 0.001) for management due to reduced access to sanitary bins. Conclusion Even though the situation in the public schools was worse, both public and private schools lack the enabling environment for MHM. School health promotion interventions, such as provision of subsidised/affordable menstrual pads and basic WASH facilities and campaigns to break the culture of silence are required for the wellbeing of girls. Other Information Published in: Tropical Medicine & International Health License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/tmi.13817